Three populisms and two dead ends: Variants of agrarian populism in Thailand - Oliver Pye; Nantawat Chatuthai (Journal of Agrarian Change, 2022)
This article discusses three forms of agrarian populism in Thailand: the “grassroots populism” of the Assembly of the Poor, the “reactionary populism” of the yellow shirts, and the “capitalist populism” of the red shirts. We examine how these three strands of populism are embedded within dynamics of agrarian change in Thailand and how the intellectual and activist orientation towards agrarian populism led to the neglect of labour, particularly agricultural migrant workers. We show how key ideological underpinnings of the Assembly's grassroots populism (Brass's “agrarian myth”) could be appropriated for the agrarian component of both reactionary and capitalist populism. Rather than a new populism, we argue that a broad and popular challenge to right-wing authoritarianism should develop inclusive class politics that embrace the rural–urban linkages that already define the social fabric of the new, rural, and agrarian precarious working class.
Keywords: 630; agrarian myth; agrarian populism; migrant agricultural workers; rural–urban linkages; Thailand